A AQUISIÇÃO DA LIBRAS POR CRIANÇAS OUVINTES FILHAS DE MÃE SURDA EM UM CONTEXTO MULTILINGUÍSTICO: UM ESTUDO DE CASO - Streiechen, Eliziane Manosso (2014)
This research aims to bring reflections on the process of acquisition/learning of the Brazilian Sign Language (Libras) by two brothers (listeners), children of a deaf mother, CODAs2, who live in a multilingual context, in a family composed by father, mother and maternal grandparents in a town in the state of Paraná. The father of the subjects is an Ukrainian descendant and therefore he speaks Portuguese with marks of the Ukrainian language. The maternal grandparents are from German origin and use both Portuguese and German to communicate. The mother only communicates in Libras, since she is deaf. More than these four languages, there is also the English language that is used by one of the subjects (subject 1), who learns it alone. Thus, we intend to examine the acquisition of Libras and the linguistic strategies used in the effectiveness of communication by the researched subjects. Assuming that the languages involved in this context are from different modalities, oral and signalized, through mother/child interaction and the managing of Libras/Portuguese languages, we postulate the hypothesis that the subjects naturally internalize the linguistic, cultural and social rules from that language. To do so, based on Stokoe (1960), Brito (1995), Quadros and Karnopp (2004), we will highlight the main linguistic parameters of sign language and also, supported in Quadros and Masutti (2007), Hall (2006), Perlin and Strobel (2008) and others, we will discuss identity issues and border zones where the bilingual subjects are involved. The records were obtained through interviews, questionnaires, videos and it was based on an ethnographic and qualitative approach using the case study. The data survey was interpreted from studies developed by Krashen (1981, 1982), Vygotsky (2008), Quadros (2008), Del Ré (2010, 2012), Krause-Lemke (2012), Sousa and Quadros (2012), among others. It was analyzed five categories composed by several segments from the subjects in interaction with their (deaf) mother in a familiar environment. These analyzis allowed us to understand that the subjects acquire Portuguese and Libras simultaneously and naturally, so both languages, Portuguese and Libras, can be considered the mother tongues of these CODAs. The deafness of the mother causes no bound or blockage in her interaction with her children, on the contrary, communication flows naturally. These CODAs used many communicative strategies with their mother, such as switching languages, gestures, bimodalism, among others. We conclude that the communicative interactions that emerged in this context bring important contributions to the linguistic development of CODAs, as well as to the area of language acquisition and education, throughout the study of the linguistic development process of children in a poorly explored context.